Proof of Work as a Three-Sided Market - Berg, Chris; Davidson, Sinclair; Potts, Jason (Frontiers in Blockchain, 2020)
Blockchain technology is the distributed ledger technology underlying Bitcoin and other cryptocurrencies. We apply Oliver Williamson's transactions cost analysis to a proof of work blockchain consensus mechanism. Blockchains reduce the costs of opportunism, but are not “trustless.” We show that blockchains are trust machines. Blockchains provide for three-sided bargaining that convert energy-intensive computation into economically-valuable trust in a proof of work context.